IMPACT OF CISPLATIN BASE CHEMOTERAPY ON QUALITY OF LIFE IN INDONESIAN PATIENTS WITH CERVICAL CANCER - Suwendar Suwendar; Achmad Fudholi; Tri Murti Andayani; Herri S. Sastramihardja (UPT Penerbitan Universitas Jember)
Cervical cancer is the most common malignantcancer of the female reproductive organs and affectsthem for a long period of time. If someone weresuffering from cervical cancer, then the quality of lifewill decline. This have been proven by research incancer patients in Dr. Sardjito Hospital includingcervical cancer [Perwitasari et al, 2011]. Not only theeffect of cervical cancer, the choice of chemotherapyregiment will also affect the quality of life(humanistic outcome) of the patients. There are avariety of chemotherapy regimens for cervicalcancer. Cisplatin-based chemotherapy regimen isrecommended by the NCCN (NationalComprehensive Cancer Network) and the Ministry ofHealth of Republic of Indonesia. Neverthelesshumanistic outcome research of these regimens arestill lacking. This study aims to evaluate the quality oflife of cervical cancer patients in Dr. Hasan SadikinHospital Bandung were treated with cisplatin basechemoterapy using the EQ-5D questionnaire.